State decoupling audit of low-carbon agricultural production - Oleksandr Datsii; Nataliia Levchenko; Ganna Shyshkanova; Ruslan Dmytrenko; George Abuselidze (Rural Sustainability Research, 2021)
It is stated that the strategic benchmark for transformational changes in the economy is currently low-carbon production, the achievement of which is possible to provide with the consistent application of an arsenal of strict control measures, in particular, the introduction of state audit of low-carbon production. The effectiveness of the mechanism for ensuring the implementation of the UN Framework Convention on Climate Change has been assessed. The necessity of implementation in the domestic practice of the state audit of low-carbon production by the decoupling approach is proved. The agri-business portfolio has been formed according to the decoupling approach as one of the leaders in greenhouse gas pollution. The author's economic and mathematical models of estimation according to the decoupling approach of the impact of branches of crop and livestock production on environmental pollution are proposed. The dependence of greenhouse gas emissions on the volume of gross output of agricultural production, capital investment and current expenditures on environmental protection has been established. The results of a comparative analysis of the realism of forecasts of changes in greenhouse gas emissions according to the methodology of the National Academy of Sciences of Ukraine and the author's methodology are highlighted. A roadmap for the introduction of a state low-carbon decoupling audit of the state decoupling audit has been proposed as part of the preparation of the second nationally determined contribution to the Paris Agreement. The expediency of supplementing GRI 300 "Environmental Disclosures" with the group of indicators GRI-305.5 "Reduction of GHG emissions", formed by the decoupling approach, is substantiated.
Keywords: 330; air pollution; greenhouse gas emissions; low-carbon production; state decoupling audit